Transition‐metal‐free Synthesis of tetra‐substituted Vinyl Iodides by Cascade Sequential Reaction of α‐Keto Acids, 1‐Iodoalkynes, and Alkyl Halides. Issue 2 (13th December 2022) - Zeng, Xiaobao; Cheng, Zhenfeng; Xie, Yushan; Gu, Yunhui
Abstract: The cascade sequential reaction of α‐keto acids, 1‐iodoalkynes, and alkyl halides are reported herein to synthesize tetra ‐substituted vinyl iodides. It represents an efficient protocol to access a diverse range of tetra ‐substituted vinyl iodides starting from simple materials in a one‐pot fashion, featuring mild reaction conditions, ease of operation, and broad substrate scope. Abstract : A transition‐metal‐free approach to access diverse tetra ‐substituted vinyl iodides by a cascade sequential reaction of α‐keto acids, 1‐iodoalkynes, and alkyl halides is established herein.